The features of anaphylactic shock in Yogyakarta, Indonesia - R.H.Yudono R.H.Yudono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1983)
An anaphylactic shock survey was carried out in Yogyakarta, Indonesia, during November December 1981. Physicians whith private practice were asked to complete the questionnaires given by the author. These questionnaires were collected without physician's identities.One hundred out of 135 respondents have had 270 patients suffering from anaphylactic shock accident. Two hundred and sixty one (96.7%) out of 270 patients had good recovery and 9 patients (3.3%) were dead. Preconditioning disturbances which made the therapy of these shocks difficult occurred in 27 patients (10 %).The drugs which caused these shocks were penicilline (27.8%). streptomycin (20%), penicilline streptomycin combination (14%), and others (38.2%). It was revealed that the route of administration of those drugs were intramuscular injection (97.4%), intravenous injection (1.1%), subcutaneous injection (1.1%). and oral administration (0.4%).Initial treatment of these shocks done by the physicians were intramuscular epinephrine (53%), intramuscular corticosteroid (23.7%), intramuscular antihistamine (15.9%), and intramuscular el-feud (1.5%). Two patients (0.7%) were immediately referred to the hospital without initial treatment given by the physicians. The rest (5.2%) had nonspecific treatment.Key Words: anaphylactic shock - allergen - penicillin - hypersensitivety - initial drug therapy